The future of traction force microscopy. (March 2018) - Colin-York, Huw; Fritzsche, Marco
Abstract: Animal cells continuously sense and respond to mechanical force. Quantifying these forces remains a major challenge in bioengineering; yet such measurements are essential for the understanding of cellular function. Traction force microscopy is one of the most successful and broadly-used force probing technologies, chosen for the simplicity of its implementation, flexibility to mimic cellular conditions, and well-established analysis pipe-line. Here, we review the accomplishments, and discuss the applicability and limitations of traction force microscopy. We explain fundamental shortcomings of the method, summarise latest improvements, and outline future pathways towards the impact of the method, especially considering latest developments in state-of-the-art super-resolution fluorescence imaging. In light of the increasing discovery of the importance of mechanobiology in cell physiology, we envisage traction force microscopy to remain a major player for quantifying mechanical forces in living cells. Highlights: Super-resolution microscopy improves the sensitivity of TFM. Stimulated emission depletion microscopy scales with its power and thus offers theoretically unlimited spatial accuracy for TFM. The increasing importance of mechanobiology in cell-biology demands further developments of TFM in near future.